An Historical Appraisal of the EU-ACP Trade Relations: Blessing or Curse? - Kingsley Osinachi N. Onu (Journal of Law Science, 2022)
There is a maxim that no man is an island. The above proclamation stands valid for country states additionally, as no country has ever effectively created with shut fringes. This demonstrates the certainty of exchange relations among countries. The Europe and the Africa, Caribbean and the Pacific (ACP) have been trading ever before the advent of slave trade up to date; and are strong trade allies up to date. It is a relationship that initially begun on the premise of business associations between early European wayfarers and indigenous anglers most particularly in the seaside regions of the Delta. This article examines these trade relations from pre-colonial period up to the extant Economic Partnership Agreement of 2007 that is being negotiated.  This article finds that it was the pre-colonial trade relations that enjoyed parity between the two parties, however, the affairs changed during the slave trade era when the trade changed from the products to the producers. This article further finds that ACP did not profit much from the subsequent agreements; this finding is hinged on the fact that after the seven centuries of the EU-ACP trade association, 39 out of the 70 ACP states remain among the Less Developed Countries. This article also finds that this poor performance can be attributed to both internal and external factors. This article advocates for a paradigm shift from the status quo to a regime where reciprocity should be based on achievement of human centered socio-economic indicators in ACP States. It further recommends the adoption of AU proposal for Common and Enhanced Trade Preference System (CETPS).